Factors associated with blood pressure variability in patients on maintenance peritoneal dialysis - Guang Xu; Ya-fei Tao; Bing Lu; Xin-hui Shi; Jiao Tao; Dong-sheng Ren (Editorial Department of Journal of Clinical Nephrology, 2023)
Objective To explore the related factors of weekly blood pressure variability (BPV) on maintenance peritoneal dialysis (MPD).Methods A total of 142 patients on MPD for at least 3 months were recruited. Blood pressure was assessed weekly by variation coefficient (CV) of systolic blood pressure in morning. The relevant clinical data was collected. The association of BPV and predictors were estimated by a mixed-effect linear model. Results Longer dialysis vintage was associated with elevated weekly BPV (P<0.05). The higher hemoglobin concentration, the greater daily fluid removal. And dosing of calcium antagonists was associated with attenuated weekly BPV (P<0.05). However, other factors (age, gender, albumin, serum calcium, serum phosphorus, parathyroid hormone, peritoneal transport features, dialysis adequacy, phosphate binders & erythropoietin) were not (P>0.05). Conclusions Weekly BPV may be affected by dialysis vintage, hemoglobin concentration, daily fluid removal and dosing of calcium antagonists.